2020
DOI: 10.4018/978-1-7998-1042-1.ch003
|View full text |Cite
|
Sign up to set email alerts
|

Food Security-Related Issues and Solutions

Abstract: The food problem has been and has remained relevant throughout the history of mankind. At the end of 20th and the beginning of the 21st century, in the lives of many nations and countries, there have been significant changes. Health status and level of education of the population, such as, for example, food security, is the priority in many countries since, in the absence of sufficient food reserves, there is an economic and political dependence of some countries on others. Having not yet received the required… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…For example, Bangladesh Rice Research Institute (BRRI) found that farmers who did not use fertilizers on their land had about 47% fewer crop yields than those who did (Naher et al, 2015). Similarly, several studies (e.g., Hossain & Ahmed, 2019;Pasko & Staurskaya, 2020) have shown that improved seeds can grow 20-30% more corps. However, food availability does not ensure access to food, though it is a pre-condition for access to and utilization of food.…”
Section: Theoretical Consideration: Link Between Food Security and Ag...mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, Bangladesh Rice Research Institute (BRRI) found that farmers who did not use fertilizers on their land had about 47% fewer crop yields than those who did (Naher et al, 2015). Similarly, several studies (e.g., Hossain & Ahmed, 2019;Pasko & Staurskaya, 2020) have shown that improved seeds can grow 20-30% more corps. However, food availability does not ensure access to food, though it is a pre-condition for access to and utilization of food.…”
Section: Theoretical Consideration: Link Between Food Security and Ag...mentioning
confidence: 82%
“…Over the past few decades, several developing countries, including Bangladesh, have achieved temporary or apparent food sufficiency through genetic improvement of food crops as well as better management of water, soil fertility, fertilizers, pests, diseases, and weeds (Denning, 2023). However, developing states still face various constraints on food production and consumption, from water scarcity to shrinking agricultural land, from excessive use of fertilizers and pesticides to growing prices of modern varieties (MVs) seeds, thereby exposing producers and consumers to greater risk (Anderson, 2019; Pasko & Staurskaya, 2020). Consequently, scarcity and mismanagement of agricultural inputs are directly related to food insecurity.…”
Section: Theoretical Consideration: Link Between Food Security and Ag...mentioning
confidence: 99%